Two new species of Ptychopteridae and Trichoceridae from the Middle Jurassic of northeastern China (Insecta: Diptera: Nematocera) - Liu, Luxi; Shih, Chungkun; Ren, Dong (Zootaxa, 2012)
Two new species of Diptera, Eoptychopterina postica sp. nov. in Ptychopteridae and Eotrichocera (Archaeotrichocera) spatiosa sp. nov. in Trichoceridae are described and illustrated from the Middle Jurassic Jiulongshan Formation of Daohugou in eastern Inner Mongolia, China. These two new species are established based on fossil specimens with bodies and complete wings.